Research on comprehensive information model of complex flexible harness under virtual environment. (2016) - Shang, Yuling; Liu, Dan; Lee, Yuan-Shin; Li, Chunquan; Zhang, Ming; Wang, Hongyang
For the disadvantage of production mode of harness manual measurement, harness automatic forming will become the development trend in the field of harness products. Among that, the information expression of harness plays an important role in harness automatic forming. Firstly, the complex flexible harness comprehensive information model (CFHCIM) is built and how to build the model is described. Then harness expression is described in detail from four aspects of auxiliary components information, electric information, connection information and harness structure information. Finally, the implementation of harness information expression from wiring model verifies the effectiveness of CFHCIM by the UG secondary development, which provides a new thought and method for information expression of harness. At the same time, CFHCIM carries out the preliminary exploration of providing information support for harness automatic forming.